Comparative Morphology of the Symbiont Cultivation Glands in the Antennae of Female Digger Wasps of the Genus Philanthus (Hymenoptera: Crabronidae) - Goettler, Wolfgang; Kaltenpoth, Martin; McDonald, Samuel; Strohm, Erhard (Frontiers in Physiology, 2022)
Females of the solitary digger wasp tribe Philanthini, called the beewolves (Hymenoptera, Crabronidae), cultivate strains of symbiotic bacteria that belong to the genus Streptomyces in unique and highly specialized glands in their antennae. The glands consist of large reservoirs that are surrounded by numerous gland cell complexes (class III). The symbionts are cultivated inside the reservoirs and are probably provisioned with nutrients secreted from the surrounding glands and/or sequestered from the hemolymph. The wasp female delivers the bacteria into the subterranean brood cell prior to oviposition. Fully grown larvae take up the bacteria and apply them to their cocoon. There the bacteria produce several antibiotics that protect the wasp offspring against fungus infestation. Hitherto Streptomyces bacteria were detected in the antennae of 38 species of the Philanthini. However, a detailed morphological analysis of the antennal glands is only available for a few species. In order to shed light on the evolutionary history of the association between beewolf wasps and bacteria, we investigated the morphology of the antennal glands of another 14 Philanthus species from the Palearctic, Paleotropic and Nearctic. We generated 3D-models of the glands based on serial semithin sections and/or micro-computer-tomography. Despite broad similarities in number and structure of antennal glands, the results revealed interspecific differences with regard to overall shape, complexity, and relative size of the reservoirs as well as the number of the surrounding gland cell units. Mapping the morphology of all species studied so far on the phylogeny (that parallels geographical distribution) revealed that related species share similarities in gland morphology, but there are notable differences between lineages. In particular, compared to the North American species the European and African species possess more complex gland structures with a higher number of gland cells. We discuss morphological, ecological and physiological aspects and provide scenarios for the evolution of the antennal glands of the Philanthini as symbiont cultivation organs.